Examination of factors that contribute to (non)vaccination of adolescents - Jerković, Lidija (Norma, 2023)
The aim of this research was to examine a group of psycho-social predictors that best distinguish vaccinated from non-vaccinated adolescents. In selecting the predictors that were examined, we relied on the results of earlier research as well as on the assumptions of the Health belief theory and the Reasoned action approach about which factors determine a person's decision to vaccinate or not. The rationale for organizing the research is the recorded trend of greater reluctance to receive the vaccine, which has become particularly pronounced in the circumstances of the coronavirus pandemic. We conducted the research on adolescents for the reason that the hesitancy towards the vaccine is most pronounced among them and at the same time the least amount of research has been conducted on them. In order to answer the research question, a cross-sectional survey was organized in which 833 respondents initially participated, so that after sorting the matrix, the sample consisted of 607 respondents (59.2% girls) aged 14 to 28 years (AS=19.00; SD=2.98). Data were collected on respondents' intention to get vaccinated, on their attitudes about the vaccine, on social norms, perceived control, on the level of knowledge about vaccines, conspiratorial beliefs, on trust in science, government and the health system, on fear of the consequences of the vaccine, on the perception of susceptibility to getting sick and the vaccination status of family members and friends. Discriminant analysis was carried out on the data and one significant function was singled out. The results reveal that over two-thirds of the surveyed adolescents have not received a single dose of the vaccine, that on average they have more negative than positive attitudes, that they have very modest knowledge about vaccines, that they significantly believe in conspiracy theories, and that they have low trust in science, government and healthcare system. The variables that best discriminate vaccinated from non-vaccinated adolescents are intention to vaccinate, positive attitudes, subjective norm, as well as knowledge and trust in science. The results favor the Reasoned action approach constructs over the Health belief theory. Overall, the results have practical implications and can serve as a basis for creating promotional campaigns and work programs with adolescents.
Keywords: Covid-19; vaccination; adolescents; Reasoned action approach; Health belief model